ESG and tax avoidance relationship: A systemic literature review - Dinarjito, Agung (Educoretax, 2026)
This study examines the correlation between Environmental, Social, and Governance (ESG) practices and corporate tax avoidance by synthesizing previous empirical research. This study utilizes a systematic literature analysis to analyze the relationship between ESG performance and disclosure and corporations' tax behavior in various institutional contexts. The review indicates a significant correlation between ESG and tax avoidance, however the nature and intensity of this association differ between situations. In numerous instances, enhanced ESG engagement correlates with reduced tax avoidance, illustrating ESG's function as an ethical governance framework that fosters openness and accountability. Nevertheless, the literature indicates that superficial implementation of ESG may serve as a legitimacy mechanism, enabling them to sustain aggressive tax practices while presenting a responsible facade. The data indicate that the impact of ESG on tax avoidance is significantly contingent upon the quality of implementation, governance frameworks, and institutional contexts. This study enhances the ESG and taxes literature by elucidating the dual function of ESG and emphasizing the significance of substance above mere symbolic compliance.